2009
DOI: 10.1111/j.1399-3038.2009.00868.x
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal aspirate cytokine levels 1 yr after severe respiratory syncytial virus infection

Abstract: Respiratory syncytial virus (RSV) infection is an important cause of recurrent wheezing in infants. Nevertheless, the link between RSV infection and wheezing has yet to be elucidated at the molecular level. Here, we present a preliminary study on the evolution of the immune response in the respiratory tract at long-term after RSV infection. Twenty-seven immune mediators were profiled in nasopharyngeal aspirates (NPAs) obtained from 20 children hospitalized due to a severe infection by RSV at discharge from hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 12 publications
2
19
0
1
Order By: Relevance
“…Respiratory viral infection alone was insufficient to induce increased levels of these Th2 cytokines. The below-sensitivity findings of IL-5 and IL-13 in our control group were also mirrored in a study by Pino et al [21]. The timing of cytokine measurements should also be mentioned, as it has been demonstrated that acute-and convalescent-phase cytokine profiles in RSV patients may differ.…”
Section: Discussionsupporting
confidence: 62%
“…Respiratory viral infection alone was insufficient to induce increased levels of these Th2 cytokines. The below-sensitivity findings of IL-5 and IL-13 in our control group were also mirrored in a study by Pino et al [21]. The timing of cytokine measurements should also be mentioned, as it has been demonstrated that acute-and convalescent-phase cytokine profiles in RSV patients may differ.…”
Section: Discussionsupporting
confidence: 62%
“…In contrast, Bermejo-Martin et al (22) found lower levels of IL-17 in nasal secretions of infants with RSV bronchiolitis at discharge as compared to admission. The same group also found IL-17 levels in nasal samples taken 1 year after an admission with RSV bronchiolitis were elevated compared with controls (23).…”
Section: Discussionmentioning
confidence: 71%
“…IL-17-producing T cells are induced in primary infections through pathways that involve STAT3 and IL-6 (16,17). High levels of IL-6 have been found in the airways of infants with RSV bronchiolitis (18,19), and a number of studies have identified IL-17 in the airways (20)(21)(22)(23)(24) and plasma (21,24) of infants with RSV infection. Two studies have found lower levels of IL-17 in the airways of the most severely affected infants, and the authors suggested that higher IL-17 levels were associated with protection against more severe disease (21,24).…”
mentioning
confidence: 99%
“…These data contrast with previous reports in which RSV infection of monolayers resulted in increased IL-6 expression [13,14,33], while work by Bem et al suggested that TRAIL might contribute to lung epithelial injury in children with severe RSV infection [17]. Like TRAIL, VEGF is a cytokine associated with RSV or rhinovirus infection in airway bronchial cells grown in monolayer [36] and has been detected in nasopharyngeal aspirates from children hospitalized with severe RSV infection [37]. However, unlike TRAIL and IL-6, in our model, VEGF was secreted at similar levels in both infected and uninfected PBEC cultures.…”
Section: Discussionmentioning
confidence: 83%